Personalized Medicine: Bridging the Gap between Genetics and Clinical Practice - Siddique, Muhammad Irfan (Asian Journal of Pharmaceutics (AJP), 2024)
Personalized medicine is a groundbreaking approach to healthcare that tailors’ treatment each patient based on their unique genetic makeup, environment, and lifestyle. A key part of this approach is pharmacogenomics, which looks at how genetic differences can affect and how patients respond to medications. By understanding how genes influence drug metabolism and effectiveness, clinicians can choose the best medications and dosages for individual patients, potentially improving treatment outcomes and minimizing side effects. This review delves into the current landscape of personalized medicine and explores how pharmacogenomics plays a role in drug response, the opportunities and challenges of bringing personalized medicine into mainstream healthcare, and where this innovative field is headed in the future. Although personalized medicine has made great strides, challenges still exist, including ethical issues, questions around cost-effectiveness, and the need for clear guidelines. Yet, with continued investment in research and addressing these hurdles, personalized medicine has the potential to significantly improve patient outcomes and transform the way healthcare is delivered.